REVITALISASI SUTAN TAKDIR ALISJAHBANA DALAM PERJUANGAN DAN PERTUMBUHAN BAHASA INDONESIA: SUATU ANALISIS ISI - Kasno Atmo Sukarto (Universitas Nasional, 2016)
ABSTRACTThe study, entitled revitalization of the STA in the struggle and the growth of Indonesian aimed to describe the backview of the STA. The theoretical basis of this study is the concept of STA in the struggle and the growth ofIndonesian. The method used in this paper is a descriptive analysis, namely, to describe things relating to matters ofthe struggle and the growth of Indonesian. The analysis in respect diancangkan 1. Indonesian language as thenational language, 2. Indonesian language teaching ., 3. The new poet concerned with literature and Indonesian, 4.the nature of Indonesian, 5. Indonesian with a high school literature, 6. Translation, 7. The guidelines for thepreparation of the new Indonesian grammar, 8. Draft Indonesian lessons in college. The result is Indonesian asnational language and state language always growing and developing dinamically.Key Word: National Languange, Indonesian language, Indonesian grammar, Indonesian lessons in college